Pathogenic variants of TUBB8 cause oocyte spindle defects by disrupting with EB1/CAKP5 interactions and potential treatment targeting microtubule acetylation through HDAC6 inhibition - Hui Luo; Jianhua Chen; Cao Li; Tian Wu; Siyue Yin; Guangping Yang; Yipin Wang; Zhihan Guo; Saifei Hu; Yanni He; Yingnan Wang; Yao Chen; et al. (Clinical and Translational Medicine, 2025)
Abstract Background Numerous pathogenic variants causing human oocyte maturation arrest have been reported on the primate‐specific TUBB8 gene. The main etiology is the dramatic reduction of tubulin α/β dimer, but still large numbers of variants remain unexplained. Methods Using microinjection mRNA and genome engineering to reintroduce the conserved pathogenic missense variants into oocytes or in generating TUBB8 variant knock‐in mouse models, we investigated that the human deleterious variants alter microtubule nucleation and spindle assembly during meiosis. Live‐cell imaging and immunofluorescence were utilised to track the dynamic expression of microtubule plus end‐tracking proteins in vivo and analysed microtubule nucleation or spindle assembly in vitro, respectively. Immunoprecipitation‐mass spectrometry and ultramicro‐quantitative proteomics were performed to identify the differential abundance proteins and affected interactome of TUBB8 protein. Results First, we observed a significant depletion of the EB1 signal upon microinjection of mutated TUBB8 mRNA (including R262Q, M300I, and D417N missense variants), indicating disruption of microtubule nucleation caused by these introduced TUBB8 missense variants. Mechanically, we demonstrated that the in vivo TUBB8‐D417N missense variant diminished the affinity of EB1 and microtubules. It also harmed the interaction between microtubules and CKAP5/TACC3, which are crucial for initiating microtubule nucleation. Attenuated Ran‐GTP pathway was also found in TUBB8‐D417N oocytes, leading to disrupted spindle assembly. Stable microtubule was largely abolished on the spindle of TUBB8‐D417N oocytes, reflected by reduced tubulin acetylation and accumulated HDAC6. More importantly, selective inhibition of HDAC6 by culturing TUBB8‐D417N oocytes with Tubacin or Tubastatin A showed morphologically normal spindle and drastically recovered polar‐body extrusion rate. These rescue results shed light on the strategy to treat meiotic defects in a certain group of TUBB8 mutated patients. Conclusion Our study provides a comprehensive mechanism elucidating how TUBB8 missense variants cause oocyte maturation arrest and offers new therapeutic avenues for treating female infertility in the clinic.